Involvement of Mouse Constitutive Androstane Receptor in Acifluorfen-Induced Liver Injury and Subsequent Tumor Development. (28th February 2016) - Kuwata, Kazunori; Inoue, Kaoru; Ichimura, Ryohei; Takahashi, Miwa; Kodama, Yukio; Shibutani, Makoto; Yoshida, Midori
Abstract: Acifluorfen (ACI), a protoporphyrinogen oxidase (PROTOX) inhibitor herbicide, promotes the accumulation of protoporphyrin IX (PPIX), and induces tumors in the rodent liver. Porphyria is a risk factor for liver tumors in humans; however, the specific mechanisms through which ACI induces hepatocarcinogenesis in rodents are unclear. Here, we investigated the mode of action of ACI-induced hepatocarcinogenesis, focusing on constitutive androstane receptor (CAR, NR1I3), which is essential for the development of rodent liver tumors in response to certain cytochrome P450 (CYP) 2B inducers. Dietary treatment with 2500 ppm ACI for up to 13 weeks increased Cyp2b10 expression in the livers of wild-type (WT) mice, but not in CAR-knockout (CARKO) mice. Microscopically, ACI treatment-induced cytotoxic changes, including hepatocellular necrosis and inflammation, and caused regenerative changes accompanied by prolonged increases in the numbers of proliferating cell nuclear antigen-positive hepatocytes in WT mice. In contrast, these cytotoxic and regenerative changes in hepatocytes were significantly attenuated, but still observed, in CARKO mice. ACI treatment also increased liver PPIX levels similarly in both genotypes; however, no morphological evidence of porphyrin deposition was found in hepatocytes from either genotype. Treatment with 2500 ppm ACI for 26 weeks after initiation with diethylnitrosamine increased the incidence and multiplicities of altered foci and adenomas in hepatocytes from WT mice; these effects were significantly reduced in CARKO mice. These results indicated that prolonged cytotoxicity in the liver was a key factor for ACI-induced hepatocarcinogenesis, and that CAR played an important role in ACI-induced liver injury and tumor development in mice.